A circle of research on disadvantaged schools, improvement and test-based accountability. (March 2020) - Huilla, Heidi
This study analyses how studies on disadvantaged schools, improvement and test-based accountability relate to each other. The analysis covers 69 studies on disadvantaged schools reported in prestigious educational journals and conducted in 1995–2015. Educational policies related to evaluation and accountability define the official goals of schooling, and the aim in this article is to analyse how the chosen studies discuss these educational policies and understand school success and failure. The following questions were asked: What typologies related to test-based accountability can be constructed in research on disadvantaged schools? What understandings of good schools are embedded in the identified typologies? Disadvantaged schools are at the centre of improvement and therefore also the target of evaluative policy practices. The results show that research supports test-based accountability practices, and that critical studies on school improvement are in the minority.